Learning From Success and Failure: Biologics for Non-approved Skin Diseases - Speeckaert, Reinhart; Lambert, Jo; van Geel, Nanja (Frontiers in Immunology, 2019)
The impressive potential of biologics has been demonstrated in psoriasis, hidradenitis suppurativa and urticaria. Numerous biologicals are entering the field for a restricted number of skin disorders. Off-label use of biologics in other recalcitrant skin diseases has increased. Mounting data point to the potential of already existing biologics acting on the IL-17/IL-23 pathway in skin disorders with epidermal hyperkeratosis (e.g. pityriasis rubra pilaris), acneiform inflammation (e.g. hidradenitis suppurativa) and loss of mucosal integrity (e.g. aphthosis). TNF-α blockers are also effective in the latter conditions but seem of particular value in granulomatous (e.g. granuloma annulare) and neutrophilic disorders (e.g. pyoderma gangrenosum). Failure of IL-17 blockade in skin diseases resulting from immune-mediated cell destruction (e.g. alopecia areata and vitiligo) illustrates its limited involvement in Th1-dependent skin immunology. Overall, disappointing results of TNF-α blockers in alopecia areata and vitiligo point to the same conclusion although promising results in toxic epidermal necrolysis suggest TNF-α exerts at least some in vivo Th1-related activities. Acting on both the Th1 and Th17 pathway, ustekinumab has a rather broad potential with interesting results in lupus and alopecia areata. The efficacy of omalizumab in bullous pemphigoid has revealed an IgE-mediated recruitment of eosinophils leading to bullae formation. Reconsidering reimbursement criteria for less common but severe diseases seems appropriate if substantial evidence is available (e.g. pityriasis rubra pilaris). For other disorders, investigator- and industry-initiated randomised clinical trials should be stimulated. They are likely to improve patient outcome and advance our understanding of challenging skin disorders.